2015
DOI: 10.1103/physreve.92.052502
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystals with patterned molecular orientation as an electrolytic active medium

Abstract: Transport of fluids and particles at the microscale is an important theme both in fundamental and applied science. One of the most successful approaches is to use an electric field, which requires the system to carry or induce electric charges. We describe a versatile approach to generate electrokinetic flows by using a liquid crystal (LC) with surface-patterned molecular orientation as an electrolyte. The surface patterning is produced by photo-alignment.In the presence of an electric field, the spatially var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 33 publications
2
107
0
Order By: Relevance
“…This suggests a reduced role for defect sharing, and that splay-matching plays a strong role in the particle docking. The localization of particles is related conceptually to particle sorting in the work by Peng et al, [20] in which splay deformation was created by photo-alignment. The complex, curved trajectory resembles the curved trajectory analyzed by Pires et al [6], and observed by Skarabot et al [21] and Nikkhou et al [8] for particles docking on a disclination line.…”
mentioning
confidence: 99%
“…This suggests a reduced role for defect sharing, and that splay-matching plays a strong role in the particle docking. The localization of particles is related conceptually to particle sorting in the work by Peng et al, [20] in which splay deformation was created by photo-alignment. The complex, curved trajectory resembles the curved trajectory analyzed by Pires et al [6], and observed by Skarabot et al [21] and Nikkhou et al [8] for particles docking on a disclination line.…”
mentioning
confidence: 99%
“…In order to study electrokinetic phenomena in realistic ranges of physical parameters, we have chosen a parameter set that corresponds to the experiments of Peng, et. al 12 . While we have shown good agreement between the numerical and experimental results, our comparison with experiments is limited by a number of factors: First, our numerical model is solved on a square domain of size ∼ 1 mm 2 or smaller, with the desired director pattern imposed throughout the cell, while the experiments are done in a chamber of dimensions 10 mm × 15 mm, with the desired pattern imposed on a 1 mm 2 region and uniform alignment on the remainder of the cell surface.…”
Section: A Numerical Methods and Choice Of Parametersmentioning
confidence: 98%
“…The field amplitude used numerically is the value of the nominal electrostatic field from the experiments of Peng, et. al 12 . Finally, the experiments use a mixture of MLC7026-000 and E7 liquid crystals at a ratio of 89.1:10.9 15 .…”
Section: A Numerical Methods and Choice Of Parametersmentioning
confidence: 98%
See 2 more Smart Citations